GAMBARAN RESILIENSI PADA REMAJA DENGAN ADVENTITIOUS VISUAL IMPAIRMENT - Pramasdwita, Angela; Erawan, Erlyn (Universitas Katolik Widya Mandala Surabaya, 2018)
Having vision is a blessing in our lives. Through vision, we can experience and feel various emotions and experiences. Losing vision can cause someone to feel negative emotions. This is a qualitative research that studies resilience in adolescents with adventitious visual impairment. Resilience is the capability to cope with obstacles and rise from negative events. This research used qualitative-inductive approach with phenomenological method, involving adolescents within the age range of 12-20, visually impaired not since birth, and have been visually impaired for 5-11 years. Data collection was done using semi-structured interview with three visually impaired adolescents. The result showed that participants experienced all aspects of resilience since they became visually impaired, including emotion regulation, impulse control, causal analysis, empathy, optimism, self-efficacy, and reaching out. Resilience helps participants to bounce back and overcome obstacles in their lives. In addition, support from their close relatives and friends help them to become more resilient.